Pengaruh Model Project Based Learning Terhadap Hasil Belajar Matematika: Ditinjau Dari Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Fitriyani, Fitriyani; Houtman, Houtman; Suroyo, Suroyo; Saabighoot, Yus Alvar (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
The purpose of the study was to determine the effect of student learning outcomes and high critical thinking through the application of project based learning learning models and to determine the effect of student learning outcomes and critical thinking using conventional learning models. The research method is a quasi-experimental and 2x2 factorial design. The research population was 159 students with a research sample of 56 students. The instruments used are questionnaires, observations and tests. Data analysis using T test and Anova test. The results of the first hypothesis data analysis obtained Fcount = 262.36 > Ftable = 4.20, the second hypothesis Fcount = 112.73 > Ftable = 4.20, the third hypothesis Fcount = 10,069 > Ftable = 4.20. The fourth hypothesis is Fcount = 10,069 > Ftable = 4,20, the fifth hypothesis is Fcount = 10,407 > Ftable = 4,20, so it can be concluded that there are differences in student learning outcomes using project based learning and conventional learning models.